Association of care fragmentation with financial and clinical outcomes of transcatheter aortic valve replacement in the US: A retrospective cohort study - Arjun Chaturvedi; Saad Mallick; Nguyen K. Le; Kevin Tabibian; Jeffrey Balian; Dariush Yalzadeh; Barzin Badiee; Radoslav Zinoviev; Peyman Benharash (PLoS ONE, 2026)
Purpose Care fragmentation (CF), defined as readmission to a non-index facility, has historically been linked with adverse clinical and financial outcomes for a variety of cardiac procedures. However, its impact on patients undergoing transcatheter aortic valve replacement (TAVR) remains understudied. Methods This retrospective study investigated the prevalence and impact of CF on outcomes of patients undergoing TAVR. All adults (≥18 years) undergoing an isolated TAVR procedure, who were readmitted within 90 days, were tabulated using the Nationwide Readmissions Database from 2016 to 2021. A 90-day readmission window was chosen in accordance with prior literature on readmission. Patients treated at a non-index facility were categorized into the CF cohort. Multivariable logistic models were developed to characterize the association of care fragmentation status with perioperative complications and resource utilization; candidate variables were selected using elastic net regularization to minimize variable collinearity. Results Of an estimated 55,891 patients who were readmitted within 90 days, 37.4% were treated at a non-index facility. While TAVR utilization more than doubled, both the readmission and care fragmentation rates fell during the study period. Following adjustment, CF status was associated with respiratory (AOR [Adjusted Odds Ratio] 1.20, 95% CI [Confidence Interval] 1.11–1.29, p < 0.001), gastrointestinal (AOR 1.21, 95% CI 1.05–1.38, p = 0.008), and infectious complications (AOR 1.17, 95% CI 1.10–1.25, p < 0.001) at readmission. Furthermore, CF was linked with greater risk of non-home discharge (AOR: 1.13 95% CI [1.03–1.25], P = 0.01). Conclusions As TAVR utilization continues to expand nationwide, further efforts to enhance care coordination and streamline information sharing are warranted to mitigate the burden of care fragmentation.